Pengaruh Loan Disburesement, Non – Performing Loan (NPL), dan Current Account Saving Account (CASA) Rasio Terhadap Profitabilitas Bank Himbara dan Bank Asing - Ghefira Nida Aulia; Maria Safitri; Agus Prayitno; Diana Puspitasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of the amount of credit disbursed (Loan Disbursement) based on economic sectors, non-performing loans (NPL), current accounts - savings accounts (CASA) on the profitability of national banks and foreign banks operating in Indonesia. The approach used is descriptive quantitative research. The data sources used in this study come from financial reports and annual reports in the banking sector. The collected data were analyzed using IBM SPSS Statistics 26 statistical software by looking at descriptive statistical tests, classical assumption tests and multiple regression analysis. The results of the study prove that only credit disbursement in the service and business sectors has a positive and significant effect on ROA, while credit disbursement in the construction, trade, and agriculture sectors has a positive but insignificant effect, and credit disbursement in the mining sector has a negative and insignificant effect. NPL has a negative but insignificant effect on ROA, while CASA has a positive and significant effect on ROA. This study confirms that bank profitability is not only determined by the volume of credit disbursement and asset quality, but is also greatly influenced by the efficiency of the funding structure as reflected in the large proportion of CASA funds. Therefore, a banking strategy focused on quality credit growth in productive sectors, consistent NPL control, and increasing the proportion of CASA funds are key factors in strengthening banking financial performance in the long term.